Metabolic phenotyping in cells and tissues using pyruvate metabolism and nuclear magnetic resonance spectroscopy - Silickas, Marius (2021)
Cellular energy metabolism is a key player in both physiological and pathological scenarios. In mouse mesenchymal stem cell populations (MSC), changes in bioenergetics are associated with differentiation into adipocyte and osteoblast lineages. As new phenotypes are adopted by differentiated cells, unique metabolic profiles are observed. On a tissue scale, metabolites associated with cellular bioenergetics (e.g. pyruvate, lactate) show potential as biomarkers for disease, such as Alzheimer’s. Changes in tissue metabolic profiles are the result of the pathological mechanisms associated with disease. Additionally, metabolites are known to reflect upstream perturbations in the proteome and the genome. Thus, detection of specific metabolite signatures is a promising approach for the interpretation of physiological and pathological processes.